The Effects of Status Mobility and Group Identity on Trust - Rémi Suchon; Marie Claire Villeval (Institute of Labor Economics (IZA), 2019)
In a laboratory experiment we test the interaction effects of status and group identity on interpersonal trust. Natural group identity is generated by school affiliation. Status (expert or agent) is awarded based on relative performance in a math quiz that is ex ante less favorable to the subjects from one group. We find that "promoted" trustors (individuals from the disadvantaged group that nevertheless achieve the status of expert) trust less both in-group and out-group trustees, compared to the other members of their group. Rather than playing against the effects of natural group identity, status promotion singles-out individuals. In contrast, trustworthiness is not affected by status and there is no evidence that interacting with promoted individuals impacts trust or trustworthiness.
Keywords: C92; D91; J62; 330; trust; status; group identity; social mobility; experiment